Nesting biology of the fungus growing ants Mycetarotes Emery (Attini, Formicidae) - Solomon, S. E.; Mueller, U. G.; Schultz, T. R.; Currie, C. R.; Price, S. L.; da Silva-Pinhati, ACO; Bacci, M.; Vasconcelos, H. L. (Birkhauser Verlag Ag, 2004)
Fungus-growing ants of the genus Mycetarotes are among the least studied in the tribe Attini. This report documents nest architecture and worker population numbers for 19 nests of M. parallelus and 5 nests of M. acutus, including the first such report for M. acutus. This new information is integrated with the scant biological information reported on Mycetarotes to date. The resulting picture of Mycetarotes life history, as well as the relative ease with which large numbers of nests can be collected and observed in the field, suggest that Mycetarotes (particularly M. parallelus) is an ideal model system for the study of coevolution of lower-attine ants and their cultivated fungi.
Keywords: Mycetarotes; nesting biology; colony size; Attini; fungus-growing ants